Prevalence and Characterization of Shiga Toxin-Producing Escherichia coli Isolated from Slaughtered Qurban Animal in Jakarta Province - Siti Gusti Ningrum; R. D. Soejoedono; H. Latif; W. Arnafia; I. W. T. Wibawan (Faculty of Animal Science, Bogor Agricultural University, 2016)
This study was conducted to investigate the presence of shiga toxin producing Escherichia coli (STEC) and the possibility of carrying rfbE gene and H7 flagellar on meat, liver, and stool samples collected from Jakarta Province of Indonesia. A total of 51 samples collected from meat, liver, and stool of slaughtered cattle from qurban festival were tested using conventional culture and multiplex PCR methods. STEC non O157 were detected in meat (5.3%) and stool (8.3%) with one isolate from stool carried H7 flagellar. However, all isolates were lacking of rfbE gene. In antimicrobial susceptibility tests, the STEC isolates showed antibiotic resistance to erythromycin and oxacillin. Overall, the result shows that meat and liver of this origin activity represents a potential risk to human health.